Health care for individuals with tuberculosis: therapeutic itinerary and flowchart proposal (Research, Society and Development, 2021)
Objective: to share the experience of developing a therapeutic itinerary in the tuberculosis care line, with the proposal of a flow chart in health care for these individuals. Methodology: qualitative study, in the experience report modality, developed by students of the Nursing Course during the theoretical-practical activities of the discipline of Health Surveillance in Primary Health Care in a municipality in the Central Region of Rio Grande do Sul, in the period from March to July 2019. Results: in the path taken between the different reference health services in the tuberculosis care line, there were weaknesses and divergences in the guidelines offered to people with suspected or diagnosed tuberculosis. The lack of a formal protocol to coordinate and direct the health care of this population implied the construction, systematization and proposal of a flow chart to be used by health services. Final Considerations: the experience contributed to the students' training process in the perspective of identifying the obstacles that permeate health care and develop strategies to overcome it, such as the proposal of a flowchart.